Concomitant Anatomic PCL and FCL Reconstructions With Partial Lateral Meniscectomy - Mark T. Banovetz BS; Jacob A. Braaten BA; Morgan D. Homan DO; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2024)
Background: Fibular collateral ligament (FCL) injuries commonly present in a multiligament knee injury pattern. These injuries are associated with significant instability leading to altered tibiofemoral biomechanics and therefore require surgical intervention. Similarly, grade 3 posterior cruciate ligament (PCL) injuries may disrupt normal tibiofemoral and patellofemoral biomechanics and increase the risk of secondary osteoarthritis. Therefore, concomitant reconstruction of the FCL and PCL should be performed to decrease knee laxity and optimize functional outcomes. Indications: Early operative treatment is indicated for patients with combined grade 3 FCL injuries and complete PCL tears. Contraindications to this procedure include patients who have significant osteoarthritis, open knee dislocations, or medical comorbidities making them unfit for surgery. Technique Description: The fundamental idea behind this technique is a stepwise treatment starting with open aspects of the procedure and followed by arthroscopic work. The technique is initiated with a lateral approach, common peroneal neurolysis, fibular and femoral FCL reconstruction tunnel preparation, and a gracilis or semitendinosus tendon autograft harvest. After that, focus shifts to intra-articular work such as associated meniscal assessment and treatment, PCL femoral and tibial tunnel preparation, graft passage, and PCL femoral tunnel fixation. Final graft fixation order is as follows: anterolateral bundle of PCL, posteromedial bundle of PCL, and finally FCL. Results: Multiple studies have reported that an anatomic FCL reconstruction in the setting of multiligament injury results in improved patient outcomes. In a prospective study of 20 patients, LaPrade et al reported −0.4 mm difference in side-to-side lateral compartment gapping and significant postoperative improvement of symptom and functional scores at a minimum 2 year postoperative follow-up after anatomic reconstruction of the FCL. Similarly, Moulton et al reported significant improvement in the average Western Ontario and Lysholm scores at 2.7 years follow-up. LaPrade et al also reported significant improvement in function and objective outcome scores at 3 years' follow-up from anatomic double-bundle PCL reconstruction. Discussion: Anatomic FCL and PCL reconstructions successfully restore near native knee objective stability and provide superior clinical outcomes when compared to nonanatomic-based FCL reconstructions that continue to be performed. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.